Gender Differences in the Perceptions of Educational Ethical Standards - Carter, Albert; Wallace, Jennifer Young; Yarbrough, Earl (Journal of Education and Training, 2024)
This manuscript reviews the use of ethical standard codes in education to determine the differences in perceptions between women and men. The ethical standards listed describe Mississippi’s Educator Code of Ethics, providing an overview of each code. Based on each of the Standards, a Mann-Whitney Wilcoxon methodology was used to determine variances in the beliefs of men and women. Results showed men and women are similar in their perceptions of ethical standards.